Islamophobia Discourse in Indonesian Media: Critical Discourse Analysis on the News of 212 Defend Islam Action on kompas.com - Taufikurakhman, Muhammad; Nizar, Moh (Wacana Publik, 2024)
As a country whose social, cultural and political structure is majorly occupied by Muslims, Islamophobia seems unlikely to be carried out by one Islamic group against another. However, in fact, Muslims in Indonesia are divided into various interest groups (madhab) that interact with each other and at the same time contest over space for actualization in the political system. This research provides preliminary evidence that Islamophobia may occur in countries that are predominantly Muslim and can be practiced by fellow Islam-based groups. Islamophobia is conducted through the mass media and constructed through the issues of radicalism, extremism and terrorism that lead to treason or overthrow of power. The motive for this discourse construction is a pro-power strategy that aims to anticipate anti-power movements carried out by the National Movement for Fatwa Defenders- 212 Indonesian Ulama Council. This conclusion is drawn based on critical discourse analysis (Norman Fairclough, 2010) which was carried out in four stages: focus on 'social irregularities', identification of barriers to addressing 'social irregularities', consideration whether social order requires this 'social irregularity' and identifying methods to solve problems. The 'social irregularity' referred to in this study is the construction of Islamophobia in the news coverage of Kompas.com in November 2016 to May 2017. The theoretical framework used in this study was Michel Foucault's Theories of Power.